Eigenvalue Problem With Two Parameters on Time Scales - Oner, Asli; Goktas, Sertac; Yilmaz, Emrah (Wiley, 2026)
In this study, two parameter eigenvalue problems were defined on time scales. This problem was reduced to a one parameter partial dynamic equation. In addition, spectral properties such realness of eigenvalue and orthogonality of eigenfunction for operator with two-parameter were investigated and some integral relations were given.
Keywords: delta derivative; delta integral; eigenvalue problems; time scales